Theory and Fieldwork - Shepherd, John; Diamond, Beverley (Canadian University Music Review / Revue de musique des universités canadiennes, 1998)
AbstractsJohn ShepherdThis intervention suggests that the recent and welcome emergence of fieldwork as a prominent feature of much current work in popular music studies has deflected attention from an undertaking that characterized the early days of popular music studies: that of developing from within the various protocols of cultural theory concepts to explain the meanings, significances, and affects that music as a socially and culturally constituted form of human expression holds for people. In tracing a shift from theoretical to ethnographic concerns in work carried out in popular music studies by musicologists, ethnomusicologists, social anthropologists, and sociologists, it is suggested that a renewed emphasis on theory in musicological work in popular music studies may be of consequence for the academic study of music as a whole.Beverley DiamondIn response to the editor's question concerning theory and fieldwork, this colloquy argues that the two are inseparable. Further, the importance of fieldwork in providing "alternative theory" which challenges the consistencies of academic thinking is emphasized. For this reason, the article eschews disciplinary history as a means of tracing important theoretical currents in music scholarship and, instead, presents arguments which confront the hegemonies of any history, any discourse of intellectual continuity, positing incidents which expose the social contingencies of theory.